Ancient canids of the Aleutian Islands (new archaeological discoveries from the Islands of Four Mountains). Issue 3 (9th May 2019) - Vasyukov, Dmitry D.; Krylovich, Olga A.; West, Dixie L.; Hatfield, Virginia; Savinetsky, Arkady B.
Abstract: We discuss the cultural roles of dog and red fox recovered from Carlisle Island, Islands of Four Mountains, Alaska, within the context of Aleutian ethnographic and zooarchaeological records. Three dog bones were recovered from the Ulyagan archaeological site, Unit 5, in levels that date to AD 1450–1645. Three red fox bones come from the Ulyagan site, Unit 4, in levels that date 460 BC–AD 95. Our analyses show that both red fox and domestic dog date earlier than the contact with Russians and that these canids do not extend west of the Islands of Four Mountains archipelago. Given the rich history of human intervention on the Aleutians ecosystems over the last 250 years, we argue that indigenous red fox inhabited the Islands of the Four Mountains region prior to western contact; however, foxes did not have a pronounced cultural role for prehistoric Aleuts. Domestic dogs accompanied humans in the Aleutians after AD 950, suggesting that these canids might be linked with the Neo-Aleut culture. In the light of Arctic and oceanic cases of human use of dogs considered in the paper, we suggest that dogs might have served as reserve food sources during long trips for people migrating west.